Analisis Harga Saham Perusahaan Pertambangan Batubara PT Bukit Asam Tbk dan PT. Aneka Tambang Tbk - Vikry Dimas Saputra; Lifatin Nada; Darmawan Darmawan (Jurnal Manajemen Bisnis Syariah, 2023)
The purpose of this research is to analyze the effect of falling coal reference unit prices in the world on the stock prices of coal mining companies in Indonesia, an analytical study of PT Bukit Asam Tbk. And PT Aneka Tambang Tbk. In this paper it is intended or useful to find out whether the fall in world coal prices has affected the stock prices of the two companies so that an investor can find out the condition of the company’s shares before and after the incident occurred. To get the results the author uses the event study method. Event study is research that observes the impact of an information announcement that affects the price of a company’s securities. Obtained from the use of non-parametric research methods, the wilcoxon signed rank test found that the company PT Bukit Asam Tbk. Not affected by this event, in another sense even though international (worldwide) coal prices are declining, even so this event does not affect the share price of this company’s coal mining company. However, it is inversely proportional to the Company PT Aneka Tambang Tbk. Because because of these events it was found that this company was affected by the consequences of these events.